Nanobiopesticides: Silica nanoparticles with spiky surfaces enable dual adhesion and enhanced performance. Issue 2 (2nd June 2020) - Zhang, Jun; Brown, Geoff; Fu, Jianye; James, Peter; Mukandiwa, Lillian; Huang, Xiaodan; Yu, Chengzhong
Abstract: Biopesticides, such as spinosad, are a new‐generation of ecofriendly pesticides in livestock industry. However, spinosad suffers from short duration of effectiveness and low potency in field conditions. Herein we report the development of a new nanospinosad design with dual adhesion and protection functions. Silica nanoparticles with spiky nanotopography loaded with spinosad possess rough surfaces. When applied topically, this nanospinosad formulation exhibited enhanced adhesion to both cattle hair and pest surface. The dual adhesion property led to significantly higher pest mortality toward tick ( Rhipicephalus microplus, an ectoparasite) than a nanospinosad formulation using nanoparticles with smooth surface and a benchmark commercial product. The adhesion performance was further quantitatively measured using rainfastness test. Moreover, solar radiation test revealed that the nanospinosad exhibited >10 times higher photostability over the commercial product. This work paves the way toward the development of high performance nanobiopesticides for sustainable agricultural applications. Abstract : Nanospinosad formulation with rough surface nanotopography has been developed for high‐efficient pests/ectoparasites treatment. This novel rough surface nanospinosad can exhibit enhanced adhesion toward both pest surface and cattle fur, leading to attractive performances including exceptional high tick mortality, greatly improved rainfastness property and robust photostability.